ANALISIS PENERAPAN PREVENTIVE MAINTENANCE MESIN PRINTING DI PT. ABC - Zamri; Sirait, Ganda (Computer Science and Industrial Engineering, 2022)
This study is to determine OEE in print shops company where company could not get good OEE value in 6 month period, peak OEE value from Jan to Jun 2020 is still low 85% more than the world leading standard. The lowest OEE percentage was in May at 19.92%, while the highest OEE value was in February at 91.19%. The OEE value indicates that the effective level of the printer's process performance is still low. The opposite is true for the substandard operating performance value, namely 68.07%. However, in February the efficiency value reached 87.05%, six major losses being a common factor that can lead to underperformance of the engine. In general, the six factors are breakdown loss, loss of setup and adjustment, small loss and stop loss, speed loss reduction, recovery loss and scrap loss. Equipment failure loss .99%, configuration and adjustment value loss 1%, small stop and stop loss 37.18%, speed loss reduction 3.28%, fault loss 0 ,60%, productivity is reduced by 0% because defective products are not di carded but will be reworked. As a result, data analysis and processing can use Pareto charts to help identify the cause of the biggest losses. According to the Pareto chart made, the six largest loss values ​​are idling and small stopping of 37.18% and reduction of speed loss, with a start-up result of 3.28%. Thus, the company can pay attention to the needs of the machine to be able to meet the needs of large-scale production.